The Impacts of Employee Turnover on Workers' Health in the United States of America - Silva, Fabiana Souza; Carvalho, George Harrison Ferreira de (Revista JRG de Estudos Acadêmicos, 2025)
This narrative review aimed to assess the impacts of employee turnover on the health of workers in the United States. High turnover rates have become increasingly frequent, especially in post-pandemic and economically unstable environments, bringing adverse effects not only to organizational productivity but also to the physical and mental health of remaining employees. The methodology included a qualitative review of scientific articles, dissertations, and theses from platforms such as Scielo, PubMed, and Google Scholar. The main findings reveal that employee turnover contributes to increased stress, anxiety, burnout, and even physical conditions such as heart disease and musculoskeletal problems. Older employees and those in insecure jobs are particularly vulnerable. Turnover also disrupts work-life balance and team dynamics, increasing the likelihood of dissatisfaction and surge the agitations. Financially, high turnover generates direct and indirect costs related to hiring, training, and productivity losses. The conclusion emphasizes that managing turnover effectively is vital to preserving not only organizational health but also individual well-being. Strategies such as individualized HR practices, mental health promotion, and predictive analytics are suggested. Ultimately, turnover affects not just the departing employees but significantly burdens those who stay behind. Further research is recommended to explore organizational-level solutions to mitigate the health impacts of high turnover.